Socio-hydrological dynamics in Bangladesh : understanding the interaction between hydrological and social processes along the Jamuna floodplain - Ferdous, Md. Ruknul (Boca Raton : CRC Press, 2020)
Bangladesh is a large delta, where most people live in the overpopulated floodplains. Flooding is a normal phenomenon, which causes much suffering. How to reduce this suffering through better managing floods is a big societal challenge. To date, societal initiatives to address this challenge mainly consist of the construction of embankments along the river bank, to control hydrological processes and discipline' the river. Yet, such embankments generate their own hydrological and societal responses in sometimes unexpected ways. The study of these interactions and feedback mechanisms between hydrological and social processes is a new academic field, one that is particularly relevant in a dynamic delta such as Bangladesh. This research sets out to explore the phenomena, opportunities and risks generated by the interactions between physical and societal processes along the Jamuna River in Bangladesh. It conceptualize these interactions as temporally dynamic and spatially diverse combinations of fighting and living with water. The research proposes the concept of "Socio-hydrological spaces (SHSs)" to enrich the study of socio-hydrology. A SHS is a geographical area in a landscape. Its particular combination of hydrological and social features gives rise to the emergence of distinct interactions and dynamics (patterns) between society and water. The SHSs concept suggests that the interactions between society and water are place-bound and specific because of differences in social processes, technological choices and opportunities, and hydrological dynamics. Through the concept of SHS, this research does not only contribute to advance the knowledge about socio-hydrological dynamics in Bangladesh, but also provides more general insights for flood risk management.
OCLC-licensed vendor bibliographic record.
Keywords: Floods -- Social aspects -- Bangladesh; Flood control -- Bangladesh; Floodplain management -- Bangladesh; SCIENCE / Environmental Science; TECHNOLOGY / Engineering / Civil